The possible psychoanalytical meanings of the mouth for mourning in the Book of Job - Zwan, Pieter van der (HTS teologiese studies, 2022)
This study is about the mouth and its parts in the book of Job on the one hand, and on psychic introjection on the other, even when these two aspects do not completely overlap. The dominance of the mouth and orality in this biblical book speaks for its symbolic and psychic implications, including dependency and depression, but also symbolisation and empathy, where psychic digestion is resymbolising what has been desymbolised by trauma. The hypothesis is therefore that the mouth plays a crucial role in the process of mourning in the Book of Job.Contribution: Interdisciplinary research into biblical texts from the perspective of psychoanalytic literary criticism adds to the broader horizons within which these texts can be analysed and interpreted. Within this frame, the focus on the mouth continues and promotes the Bodies Studies movement, which has been blossoming for over 40 years.